Movimiento estudiantil y violencia. Los casos de Madrid (1968-1970) y Santiago de Chile (1984-1986) - Javiera Errázuriz Tagle (Nuevo mundo - Mundos Nuevos, 2009)
This paper aims at exploring the relationship between the student movement and the repressive authority in the context of an authoritarian political regime. The student movement is formed by physical bodies susceptible to situations of violence that may range from the most shocking physical attacks to more subtle actions that can be nearly imperceptible but nonetheless harmful. However, we are not only interested in exploring the repression against the students; but we also aim at analyzing the circulation of violence between the student factions and the repressive authority, as well as the dynamics generated by this interaction. The Chilean and the Spanish cases represent two examples of student movements developed under the shadow of authoritarian political regimes. Both show a different repertoire of collective actions, shaped by the different dynamics that they generated with the repressive authority. We are interested in exploring “the efficacy of violence in collective action repertoires”, which we understand not only as a reaction to repression, but also as a call to action by the movements.